Re-Design Interior Cafe “Aicon Coffe And Donuts” Dengan Konsep Modern Minimalis - Wendhi Agusdi; Heldi Heldi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
. In the modern era, cafés have become a popular place for students and the public to socialise and work. The importance of unique and comfortable interior design drives intense competition in this industry. This study focuses on the interior re-design of ‘Aicon Coffee and Donuts’ café in Padang, which faced spatial, comfort and aesthetic issues. The 4D method (Define, Design, Develop, Disseminate) was used for design analysis and development, with primary and secondary data. Results show the importance of a minimalist modern concept that emphasises simplicity, functionality and aesthetics. This design creates a comfortable and attractive space for visitors with the use of colours, quality materials, and efficient spatial arrangement. The re-design is expected to increase the attractiveness of the cafe and provide a better experience for visitors.